Permainan Edukasi Ular Tangga: Menumbuhkan Minat Belajar Bahasa Inggris Anak-Anak di Gampong Lubok Sukon - Meutia, Putri Dini; Suryani; Lubis, Silvi Puspa Widya; Fatimah, Siti (Pendidikan Matematika, FKIP Universitas Mataram, 2025)
Gampong Lubok Sukon, located in Ingin Jaya District of Aceh Besar Regency, is one of the tourist villages in Aceh Besar. The village’s appeal lies in its preserved natural beauty and the maintenance of its ancestral cultural heritage. Rumoh Aceh is a significant attraction for local and international tourists visiting the village. Based on the interview conducted, most visitors to the village are foreigners. This influx of foreign visitors allows the children in the village to develop their foreign language skills. However, those children interact less with this foreigner due to their limited vocabulary. Therefore, the team is interested in organizing a community service activity in that village. This activity aims to enhance the childern’s English vocabulary through the educational game of Snake and Ladders. This activity involves 20 elementary school students from Gampong Lubok Sukon. The result of this activity shows that the participating children are highly enthusiastic in answering the questions provided. The respondents showed interest in learning English through Snake and Ladders game and their vocabulary improved.